Aerodynamic results from the star hover test: an examination of active twist actuation - Bauknecht, A.; Ewers, B.; Schneider, O.; Raffel, M. (My University, 2015)
Active rotor control concepts, such as active twist actuation, have the potential to effectively reduce the noise and vibrations of helicopter rotors. Within the STAR (Smart Twisting Active Rotor) hover test, an active twist rotor was tested in the rotor preparation hall at DLR Braunschweig. The rotor blades were actuated with frequencies of 1/rev- 5/rev and peak torsion amplitudes of up to 2_. This paper describes aerodynamic results from the hover test based on time-resolved stereoscopic PIV measurements at the forward blade tip position. Continuous time series of flow fields behind the blade tips were evaluated to investigate the young blade tip vortices between yv = 3:56_ and 45:74_ of vortex age. For the unactuated baseline case, the vortex trajectory, blade tip scattering, and temporal development of the peak axial and swirl velocity are discussed. The effects of the active twist actuation on the blade tip vortices are examined for the 1=rev and 3=rev actuation frequencies. The variation of the vortex trajectories is dominated by the blade tip deflection for the 1=rev actuation, and by the torsion of the blade tip for the 3=rev actuation. The 3=rev actuation reduces the initial peak swirl velocity by up to 35% compared to the baseline case. The actuation with the control phase angles j3 = 45_??135_ achieves a strong variation of the vortex trajectories with a vertical deviation of up to 2:6%R below the rotor tip path plane. The present aerodynamic investigation reveals a high control authority of the actuators – especially for the 3=rev actuation frequency – on the vortex trajectories and the vortex strength, thus demonstrating the usefulness of the active twist concept.
Keywords: Aerodynamics